Analysis of Factors Affecting the Timeliness of Data Reporting in the Information System and Monitoring on the ASPAK Application at the South Suwawa Health Center - Jainun Paulu; Herlina Jusuf; Nikmatisni Arsad (Universitas Muhammadiyah Palu, 2026)
ASPAK (Medical Facilities, Infrastructure, and Devices Application) is a web-based application to manage and monitor health facility data. This study aims to analyze the factors that affect the timeliness of data reporting at the South Suwawa Health Center through the ASPAK application in the Health Center Management Information System (SIMPUS). The factors studied include information system quality, user competence, management support, technological infrastructure, and human resources. Data were collected through a survey of 44 Puskesmas employees and analyzed using simple linear regression and cross-tabulation. The results showed that most employees gave positive assessments of the quality of information systems (75%), user competence (79.5%), management support (68.2%), technological infrastructure (70.5%), and human resources (52.3%). The timeliness of data reporting is also relatively high with 61.4% reporting on time. The regression analysis confirmed that these five factors had a significant effect on the timeliness of reporting with a significance value of < 0.05 and a determination coefficient (R²) of 40.3%. Research suggests improved training, management support, and infrastructure development to improve the timeliness of data reporting.